Failure Analysis of Spacecraft Onboard Control Complexes under the Influence of Space Environment Factors - Oshmanova, Aizhan (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2026)
During the operation of spacecraft (SC) designed for various purposes, failures occur in onboard electronic equipment, which may lead to the development of off-nominal situations and, in some cases, to the loss of satellites. As a rule, such failures arise in the spacecraft onboard control system (OCS). Many researchers attribute these failures to the effects of ionizing radiation in near-Earth space (NES). Therefore, assessing the performance of the spacecraft onboard control system under the combined influence of near-Earth space environmental factors is both critical and necessary. The aim of this study is to assess the reliability of onboard electronic equipment by taking into account radiation-induced failures of various types using directed graph structures. In this work, a reliability parameter for spacecraft control systems based on the direction of error propagation is developed. Directed graphs of the onboard control system characterizing error propagation are presented. A directed graph model of the onboard control system is considered, in which system elements and their interconnections are represented by vertices and edges. Based on the probabilistic characteristics of functional modules, a methodology is developed for identifying error propagation directions that determine the greatest structural vulnerability of the system. It is shown that the reliability of the onboard control system is determined by the system architecture rather than by random fluctuations of model parameters. The proposed reliability parameter makes it possible to identify vulnerabilities of functional nodes that affect the operation of the control system under the combined influence of space environment factors. The obtained results can be used in the design of spacecraft onboard control systems in order to enhance their reliability and resistance to the combined effects of space environment factors and operating conditions.